2006
DOI: 10.21236/ada457329
|View full text |Cite
|
Sign up to set email alerts
|

Determination of MS2 Bacteriophage Stability at Low pH Using the Integrated Virus Detection System (IVDS)

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The observed data shows that γ-PGA increases survival of MS2 bacteriophage when it is exposed to increasing temperatures including 37 °C, 50 °C and 60 °C ( Figure 4 ). A previous study using the integrated virus detection system (IVDS) found MS2 phages can be detected when temperatures are increased to 63 °C for half an hour, but longer exposure or increasing temperature results in a quick decrease in detectable MS2 particles [ 30 ]. However, we show here that MS2 phages without γ-PGA were detected even after 24 h of exposure to 60 °C but with very low viable number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed data shows that γ-PGA increases survival of MS2 bacteriophage when it is exposed to increasing temperatures including 37 °C, 50 °C and 60 °C ( Figure 4 ). A previous study using the integrated virus detection system (IVDS) found MS2 phages can be detected when temperatures are increased to 63 °C for half an hour, but longer exposure or increasing temperature results in a quick decrease in detectable MS2 particles [ 30 ]. However, we show here that MS2 phages without γ-PGA were detected even after 24 h of exposure to 60 °C but with very low viable number.…”
Section: Discussionmentioning
confidence: 99%
“…Phage MS2 is stable over a wide range of pH values. Previous work has found MS2 is stable under strong acidic conditions as low as pH 1.4 [ 30 ]. This may explain why we did not observe a difference in formulated and non-formulated MS2 viability.…”
Section: Discussionmentioning
confidence: 99%
“…ES-DMA has been previously used to measure the size of both large and small viruses including adenovirus (including strain MAD-K87), , rhinovirus (HRV2 and HRV14), , rice yellow mottle virus (RYMV), , cowpea mosaic virus (CPMV), MS2, , cowpea chlorotic mottle virus (CCMV), reo-3 reovirus, and the Kilham rat virus (KRV) . Viruses with tubular components such as T2, T4, λ-phage, and tobacco mosaic virus (TMV) have also been analyzed.…”
mentioning
confidence: 99%
“…As shown in Figure 4, the MS2 peak shows a count of 3 counts in the 21.67 -25.9 nm range in the ROI. The large peaks at 16.3 and 17.5 nm are indicative of the protein breakdown products from MS2 that has been disrupted due to chemical means [6,7].…”
Section: Chlorinated Water Samplesmentioning
confidence: 99%